Penyiapan Starter Kering Bakteri Asam Laktat Halofilik untuk Pengolahan Hasil Perikanan Fermentatif Bergaram - Ustadi Ustadi; Suparmo Suparmo; Endang Sri Rahayu (agriTECH, 2002)
Lactic acid bacteria (LAB) is known as fermentation agent in traditional food fermentation products in Indonesia, which also include fish products. Objectives of this research were to select LAB strain isolated from peda, terasi, salted fish and bekasam which were potential for dry starter preparation. This research were consisted of three parts : (a) selection of halophilic LAB strain (b) dry starter preparation by addition glycerol protectant, sucrose and starter neutralization and further testing its viability upon storage and (c) ability of the selected isolate to inhibit pathogenic and spoilage bacteria. Results of this reseacrh indicated there were 8 moderate halophilic LAB, they were Lb. plantarum (isolate EDI-14, DES-21, DES-24, and DES-26), Leuc. paramesenteroides (isolate DAN-7 and DAN-7), and Lv. casei subsp. casei (isolateDES-27). Addition of 5% glycerol protects LAB viability during storage. Addition of 17.7% sucrose in the media and neutralized the pH increase LAB viability during storage. Within 5 weeks of storage. The viability of Leuc. paramesenteroides (DAN-7) and Lb. plantarum (DES-26) decrease 10.4% (from 33 x 107 sel/g to 3.3 x 107 sel/g dried starter) and 9.77% (from 36 x 107 sel/g to 3.5 x 107 sel/g dried starter), respectively. Freeze drying process and dry storage did not affect the LAB isolate towards inhibiting the pathogenic bacteria and spoilage bacteria such as Salmonella choleraesius JCM 3919, Shigella, Escherichia coli FNCC 0091, Vibrio parahaemolyticus JCM 2147 (gram negative), Staphylococcus aureus FNCC 0091, and Morganella morganii NCTC 2847 (gram positive).